Measuring the Utilization and Occupancy of Desktop Computers in laboratories of Sikh National College, Qadian, a case study - Kumar, Koushal (INFOCOMP Journal of Computer Science, 2019)
Computers have become a vital and irreplaceable part of college or university students lives. While initially conceived as a simple instrument for enhancing instructional experience, computers are now have been used in all facets of student life. Colleges and universities these days are now bound to provide sufficient amount of computing resources to their students in computer labs. The computer equipped libraries are not only making academic work easier for pupil but also helping in bettering academic collaboration among students from different college and universities. This paper analyzes and find out the empirical results on the occupancy and usage of computers in the central library of our Sikh National college, Qadian, Gurdaspur, Punjab, India. The study conducted will reveals a vital question i.e., Do students still comes in library and accesses to computers in the library even in mobile phone and laptop era? The significance of our research is that it will help Library administrators in installing more computers in the library when the library is overloaded during peak hours. For solving our research problem we are going to apply statistical T-test. We have collected real time data from our college library in regular interval of time and for implementation purposes we have used “R language” with RStudio as an environment.